2005
DOI: 10.1177/0959680105053966
|View full text |Cite
|
Sign up to set email alerts
|

Academic Employment and Gender: A Turkish Challenge to Vertical Sex Segregation

Abstract: ▪ This article explores the paradox of women's academic employment in Turkey. There is a low rate of female labour market participation in the formal sector, yet a higher proportion of women professors than in any of the 25 European Union countries. We use a range of data to set the Turkish labour market and its higher education sector in comparative European perspective, then present findings from two qualitative studies of Turkish professors, concluding that ideological state support rather than legal framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…(For details refer to: Acar, 1983Acar, , 1989Acar, , 1990aAcar, , 1990bAcar, , 1991Acar, , 1996Acar, , 1998aAcar, , 1998bCindogdu & Muradoglu, 1996;Ergü n, 1978;Gü nlü k Ş enesen, 1996;Healy et al, 2005;Kö ker, 1988;Kurnaz, 1996;Ö ncü , 1979;Ozbilgin & Woodward, 2003;Ö zkanlı & Korkmaz, 2000a;Spuler, 1975). Generally, most Turkish academic women consider that there is no gender discrimination in either academic promotion or management, but they report that their careers are seriously affected by role conflict (Acar, 1983(Acar, , 1986(Acar, , 1990a(Acar, , 1991(Acar, , 1996(Acar, , 1998bCindogdu & Muradoglu, 1996;Erkut, 1982;Kö ker, 1988;Ö zkanlı & Korkmaz, 2000bÖ zkanlı & Korkmaz, , 2000c.…”
Section: Resultsmentioning
confidence: 97%
“…(For details refer to: Acar, 1983Acar, , 1989Acar, , 1990aAcar, , 1990bAcar, , 1991Acar, , 1996Acar, , 1998aAcar, , 1998bCindogdu & Muradoglu, 1996;Ergü n, 1978;Gü nlü k Ş enesen, 1996;Healy et al, 2005;Kö ker, 1988;Kurnaz, 1996;Ö ncü , 1979;Ozbilgin & Woodward, 2003;Ö zkanlı & Korkmaz, 2000a;Spuler, 1975). Generally, most Turkish academic women consider that there is no gender discrimination in either academic promotion or management, but they report that their careers are seriously affected by role conflict (Acar, 1983(Acar, , 1986(Acar, , 1990a(Acar, , 1991(Acar, , 1996(Acar, , 1998bCindogdu & Muradoglu, 1996;Erkut, 1982;Kö ker, 1988;Ö zkanlı & Korkmaz, 2000bÖ zkanlı & Korkmaz, , 2000c.…”
Section: Resultsmentioning
confidence: 97%
“…This is surprising given that research into employment phenomena in different organizational contexts, including issues related to equality and diversity e.g. Healy, Bradley and Forson, 2011;Healy, Özbilgin and Aliefendioglu, 2005), has demonstrated that the three dimensions are inter-related and should not be considered in isolation from each other (e.g. Seierstad and Healy, 2012;Tatli and Özbilgin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gender differences in pay are greater in universities where salaries are determined using discretionary judgments of merit rather than seniority (Warman et al, 2010). Conversely, in Turkey, where there is a highly transparent promotion system, women are strikingly well-represented within the full professor rank (Healy, Özbilgin and Aliefendio lu, 2005).…”
Section: Characteristics Of Pay Systemsmentioning
confidence: 99%